Effect of cinnamon, cardamom, saffron and ginger consumption on blood pressure and a marker of endothelial function in patients with type 2 diabetes mellitus: A randomized controlled clinical trial. (3rd May 2016) - Azimi, Paria; Ghiasvand, Reza; Feizi, Awat; Hosseinzadeh, Javad; Bahreynian, Maryam; Hariri, Mitra; Khosravi-Boroujeni, Hossein
Abstract: Herbal medicines with high amounts of phytochemicals have been shown to have beneficial effects on blood pressure (BP), endothelial function and anthropometric measures. This study aimed to determine the effect of herbal treatment on BP, endothelial function and anthropometric measures in patients with type 2 diabetes mellitus (T2DM). This clinical trial included 204 T2DM patients randomly assigned to four intervention groups receiving 3 g cinnamon, 3 g cardamom, 1 g saffron or 3 g ginger with three glasses of black tea, and one control group consuming only three glasses of tea without any herbals, for 8 weeks. Intercellular adhesion molecule-1 (ICAM-1), systolic and diastolic BP and anthropometric measures were collected at baseline and after 8 weeks. No significant difference was found between various medicinal plants in terms of influencing BP, serum soluble (s)ICAM-1 concentrations and anthropometric measures. However, in within-group comparison saffron and ginger intakes significantly reduced sICAM-1 concentrations (340.9 ± 14.4 vs 339.69 ± 14.4 ng/ml, p = 0.01, and 391.78 ± 16.0 vs 390.97 ± 15.8 ng/ml, p = 0.009, respectively) and ginger intake affected systolic BP (143.06 ± 0.2 vs 142.07 ± 0.2 mmHg, p = 0.02). Although administration of these herbal medicines as supplementary remedies could affect BP and sICAM-1 concentrations, there was no significant difference between the plants in terms of influencing anthropometric measures, BP and endothelial function.